A vision to reach for: the interplay between visual perception and visually-guided movements - Nissens, Tom; Justus Liebig University Giessen (My University, 2020)
Throughout everyday life we are surrounded by a multitude of stimuli we can look at, reach to, and visually perceive in many different ways. However, we cannot perceive, look at, or reach to all stimuli simultaneously. We have to make a selection to perceive and interact with the world in a useful way. The selection for perception, saccades and reaches is the consequence of activation and competition on specific priority maps. Where we select to perceive influences the selection for action, and vice versa. For example, a movement trajectory is influenced by the presence of a physically salient distractor. Previous research has mainly focused on the interplay between visual perception and eye movements. However, less is known regarding how reaching movements are influenced by visual perception and eye movements. The studies in this thesis were designed to get a better understanding of the mechanism by which visually guided reaching movements are influenced by the motor and sensory component of the visual system. In the first study, I investigated whether the target selection for saccades and reaches occur independently. I analyzed trajectories of simultaneously performed saccades and reaches. If the target selection for both effectors were independent, I expected to observe no difference in the movement trajectory depending on the other effector s target location. However, I found that movements curved away from the other effector s target location for both reaches and saccades. Previous research showed that the top-down task set can trigger an active suppression of physically salient distractors during selection for perception and saccades. By actively suppressing the distractor location the attraction of visual perception and saccades can be avoided. It was unclear whether this mechanism also transferred to reaching movement planning. In the second study, I investigated whether the influence of a physically salient distractor on reaching movements is task-dependent. I compared trajectories of reaches towards a target when a physically salient distractor was present between two tasks. In the first task the target had to be searched. In the second task the target was cued. Hence, the target certainty was low in the first task but high in the second task. We hypothesized that only in the second task, when the target certainty was high, the distractor could be actively suppressed during reach planning, avoiding attraction towards the distractor s location. I found reaching movements to curve away from the physically salient distractor in the search-to-reach task but not in the cued reach task. Stimuli associated with reward influence where we perceive, look and reach. A large body of research has delved into the mechanisms of how reward influences perception and saccades. However, the mechanisms of how reward influences reaching movements is not well understood. In the third study I wanted to clarify two open standing points: (i) is the attraction of reaches towards reward the result of an association between reward and a color or between reward and reaching to a color? (ii) Is the attraction of reaches towards reward dependent on an initial attraction by physical salience? To this end I designed a task in which a non-physically salient distractor signaled the possibility of earning either low or high reward. I found that reaching movements curved towards the non-salient, reward signaling distractor. Note that reaching towards the reward signal was never necessary nor useful as it would lead to the omission of reward. Furthermore, the attraction by reward was enhanced in short latency reaches.The results of these studies show that the planning of reaching movements is influenced by the selection for perception and saccades. The interplay between the selection of visual perception and visually-guided action fit within a priority framework where activation on different priority maps is transferred. Under certain circumstances, the transfer of activation results in competition on the movement priority map during movement planning. The competition affects movement parameters and is responsible for the observed interplays between perception and action.
Keywords: Reaching; visual search; saccades; visually-guided movements; attention; priority; ddc:150